RISIKO KETERLAMBATAN PERKEMBANGAN BAYI BERAT LAHIR RENDAH (BBLR) DENGAN HIPERBILIRUBINEMIA PADA UMUR 3 BULAN - , I GST AG GD AG. WIRADHARMA ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Developmental delay since prenatal, perinatal or postnatal periode can occur because of variety factors, of them low birth weight infant and hyperbilirubinemia. This study to find the major risk of the developmental delay occurrence in infants aged 3 months with low birth weight who had suffered from hyperbilirubinemia compared with those without hyperbilirubinemia. This is a prospective cohort study. The subjects of this study were the low birth weight infants suffering hyperbilirubinemia whose met the inclusion and exclusion criteria. The sample size of this study was 46 infants. The developmental delay measured using Mullen Scaleâs of Early Learning (MSEL) instrument and being analyzed with chi square test and calculate the relative risk with significancy level p < 0.05. Risk of developmental delay in 3 month old in low birth weight small gestasional age infants than low birth weight appropriate gestasional age is 14 times in small gestasional age with 95% confident interval (1,104-193,235) and p value 0,042 and in hyperbilirubinemia 1.5 times than without hyperbillirubinemia with 95% confident interval (0,288-7,476). Hyperbilirubinemia and low birth weight small gestasional age is a risk factor for developmental delay in infants aged 3 months old.